2008
DOI: 10.1557/mrs2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of β-Hairpin Peptides for Material Construction

Abstract: Self-assembled materials composed of beta-sheet forming peptides hold promise as therapeutics and novel biomaterials. This article focuses on the design and engineering of amphiphilic peptide sequences, especially beta-hairpins. Peptides can be designed to intramolecularly fold and then self-assemble on cue, affording hydrogels rich in beta-sheet structure. Hydrogels having distinct material properties can be designed at the molecular level by modulating either the peptide's sequence or the environmental stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…Specifically, these hydrogels were found to exhibit minimal-to-no cytotoxicity to a variety of cell lines including NIH3T3 murine fibroblasts, C3H10T1/2 mesenchymal stem cells, hepatocytes, MG63 osteoblast progenitor cells, and primary articular chondrocytes [410,411,466,467]. The homogeneous distribution C3H10T1/2 cells in MAX8 and MAX1 hydrogels is dependent on the gelation kinetics.…”
Section: Shear Stress Responsive Hydrogelsmentioning
confidence: 99%
“…Specifically, these hydrogels were found to exhibit minimal-to-no cytotoxicity to a variety of cell lines including NIH3T3 murine fibroblasts, C3H10T1/2 mesenchymal stem cells, hepatocytes, MG63 osteoblast progenitor cells, and primary articular chondrocytes [410,411,466,467]. The homogeneous distribution C3H10T1/2 cells in MAX8 and MAX1 hydrogels is dependent on the gelation kinetics.…”
Section: Shear Stress Responsive Hydrogelsmentioning
confidence: 99%
“…4A). This significant increase in solubility is largely due to the eight lysines contained within the SVS-1 sequence, which at physiologic pH are protonated [23]. CD spectroscopy confirmed that conjugation of PTX to PEG-GG-SVS-1 did not prevent folding of the peptide at the surface of phosphatidylserine containing liposomes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These domains can be spatially separated either along the length of the molecule or along a defined face of the folded molecule. 39 The hydrophilic segments can either be uncharged (polar) or charged (cationic, anionic or zwitterionic) 40 . While such segments are spatially segregated in lipids, in amphipathic peptides the primary sequences contain alternating or random segments of hydrophobic and hydrophilic residues.…”
Section: Structures Of Self-assembling Nanoparticlesmentioning
confidence: 99%
“…103 Glycol-, peptide- and silicon-capped dendrimers have been synthesized using carbohydrates, peptides and silicon. 39,105 Drugs can associate with dendrimers through physical entrapment within the void spaces or by attachment of the pro-drug to functional groups positioned on the dendrimer surface. 94 …”
Section: Structures Of Self-assembling Nanoparticlesmentioning
confidence: 99%